Fractional Model for the Flow of Casson Nanofluid using the Generalized Fourierâs Law for Heat Transfer - Sheikh, N.A. (Springer Science and Business Media B.V., 2021)
The present work used a fractional model of Casson fluid by utilizing a generalized Fourier's Law to construct Caputo Fractional model. A flow of nanofluid flowing in a channel is considered with free convection and electrical conduction. A novel transformation is applied for the energy equation and then solved using integral transforms, combined, the Fourier and Laplace transformations. The results are shown in the form of the MittagâLeffler function. The influence of physical parameters has been presented in graphs and tables and discussed in this work. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.